2002
DOI: 10.1081/sta-120013018
|View full text |Cite
|
Sign up to set email alerts
|

ESTIMATION OFCpFOR AUTOCORRELATED DATA AND MEASUREMENT ERRORS

Abstract: The properties of the estimator of C p for autocorrelated data in presence of measurement errors are discussed. This work is motivated by the fact that while some efforts have been dedicated in the literature to the statistical properties of the capability index estimator when the data are autocorrelated, scarce attention has been given to the evaluation of these properties when sample data are affected by measurement errors. In this paper, for a first order stationary autoregressive process, the performances … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 8 publications
0
20
0
Order By: Relevance
“…Pearn et al [13] conducted a sensitivity analysis of C p and C pm in the presence of gauge measurement errors, and Scagliarini [14] examined the joint condition of "autocorrelation and measurement errors" by analysing the properties of the C p estimator for autocorrelated data in the presence of measurement errors.…”
Section: Scagliarinimentioning
confidence: 99%
“…Pearn et al [13] conducted a sensitivity analysis of C p and C pm in the presence of gauge measurement errors, and Scagliarini [14] examined the joint condition of "autocorrelation and measurement errors" by analysing the properties of the C p estimator for autocorrelated data in the presence of measurement errors.…”
Section: Scagliarinimentioning
confidence: 99%
“…However, according to Kotz & Johnson (1993), approximate expressions can be derived by statistical differential method (Scagliarini 2002),…”
Section: Estimating C P With Autocorrelated Datamentioning
confidence: 99%
“…He shows, through simulations, that if autocorrelation is ignored when calculating confidence intervals, the empirical coverage rate differs considerably from the nominal one. Some further studies dealing with capability indices and autocorrelated data can be found in Noorossana 18 , Scagliarini 19 , and Chen et al 20 .…”
Section: Introductionmentioning
confidence: 97%